1998
DOI: 10.1007/s004410051058
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of interstitial cells of Cajal in the mouse colon by vital staining

Abstract: Interstitial cells of Cajal (ICCs) are believed to be a major element in generating the spontaneous rhythm of the gastrointestinal tract. A prominent problem in the study of these cells has been the difficulty in observing them in intact tissues. We used the lipophilic dye DiI to stain ICCs in the submucosal-circular muscle border of freshly dissected mouse colon. The placement of small DiI crystals in this area resulted in the labeling of ICC-like cells. Two main morphological cell types, viz., bipolar and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
(29 reference statements)
0
12
0
1
Order By: Relevance
“…One such dye of low cell toxicity may be the lipophilic DiI (see Hanani et al, 1999). Recently, it was demonstrated in the mouse colon that DiI under appropriate conditions labeled cells that under the TEM were identified as ICC (Hanani et al, 1998). The ultrastructure of the labeled cells was preserved, together with contacts with nerves and smooth muscle cells.…”
Section: Osmic Acid/zinc Iodide (Champy-maillet Method)mentioning
confidence: 99%
“…One such dye of low cell toxicity may be the lipophilic DiI (see Hanani et al, 1999). Recently, it was demonstrated in the mouse colon that DiI under appropriate conditions labeled cells that under the TEM were identified as ICC (Hanani et al, 1998). The ultrastructure of the labeled cells was preserved, together with contacts with nerves and smooth muscle cells.…”
Section: Osmic Acid/zinc Iodide (Champy-maillet Method)mentioning
confidence: 99%
“…Hanani et al observed ICC in living tissue and showed its network properties using Nomarski optics and Lucifer yellow injection [5]. The present method expands on this technical achievement by the development of a preparation that allows patch clamp recording from ICC, which can now also be applied to other auxiliary cells such as glial cells [6].…”
Section: Resultsmentioning
confidence: 85%
“…The cells were found along the submucosal border of the circular muscle layer in apposition to smooth muscle cells and nerve endings. The cells had all the structural characteristics of ICC: they were rich with caveolae and mitochondria and had discontinuous basal lamina (see Hanani et al, 1998).…”
Section: Results and Discussion Visualization Of Living Dii-labeled Imentioning
confidence: 99%
“…Staining with DiI was performed as described previously (Hanani et al, 1998). Briefly, DiI (Molecular Probes) was dissolved at 3% in DMSO; this solution was diluted to 0.15% DiI in 96% ethanol and was further diluted to 0.003% in Krebs solution, causing precipitation of the dye as small crystals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation